2021
DOI: 10.3390/molecules26123482
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Squaramide-Conjugated Fibroblast Activation Protein Inhibitor-Based Agents AAZTA5.SA.FAPi and DOTA.SA.FAPi

Abstract: Recently, the first squaramide-(SA) containing FAP inhibitor-derived radiotracers were introduced. DATA5m.SA.FAPi and DOTA.SA.FAPi with their non-radioactive complexes showed high affinity and selectivity for FAP. After a successful preclinical study with [68Ga]Ga-DOTA.SA.FAPi, the first patient studies were realized for both compounds. Here, we present a new squaramide-containing compound targeting FAP, based on the AAZTA5 chelator 1,4-bis-(carboxylmethyl)-6-[bis-(carboxymethyl)-amino-6-pentanoic-acid]-perhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Several derivatives have shown promising clinical results, including FAPI-02 ( 16 ), FAPI-04 ( 17 ), FAPI-46 ( 18 ), FAPI-34 ( 19 ), FAPI-74 ( 20 ), DOTA.SA.FAPI and DATA5m.SA.FAPI ( 21 ), DOTA-2P(FAPI) 2 ( 22 ), and FAPI-42 ( 23 ). Many derivatives are being developed, and some promising preclinical data have been obtained, such as 18 F-fluoroglycosylation-FAPI ( 18 F-FGlc-FAPI) ( 24 ), QCP01 and QCP02 ( 25 ), and AAZTA5.SA.FAPI ( 26 ) ( Table 1 ).…”
Section: Targeting Cafs For Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several derivatives have shown promising clinical results, including FAPI-02 ( 16 ), FAPI-04 ( 17 ), FAPI-46 ( 18 ), FAPI-34 ( 19 ), FAPI-74 ( 20 ), DOTA.SA.FAPI and DATA5m.SA.FAPI ( 21 ), DOTA-2P(FAPI) 2 ( 22 ), and FAPI-42 ( 23 ). Many derivatives are being developed, and some promising preclinical data have been obtained, such as 18 F-fluoroglycosylation-FAPI ( 18 F-FGlc-FAPI) ( 24 ), QCP01 and QCP02 ( 25 ), and AAZTA5.SA.FAPI ( 26 ) ( Table 1 ).…”
Section: Targeting Cafs For Imagingmentioning
confidence: 99%
“…In clinical studies, 68 Ga-DATA5m.SA.FAPI PET/CT showed specific uptake in focal nodular hyperplasia in the liver ( 35 ), and there was no significant difference in tumor uptake between 68Ga-DOTA.SA.FAPI and 18 F-FDG compared with 18 F-FDG in 14 types of tumor imaging in a total of 54 patients, with the exception of brain metastatic lesions ( 27 ). Next, the team found that radiolabeling SA.FAPI with AAZTA5 as a chelator (i.e., AAZTA5.SA.FAPI) was superior to both DOTA and DATA5m in terms of labeling process and drug yield, and the IC 50 of the product was in the low nanomolar range (0.55–0.57 nM), but the drug is still in preclinical studies ( 26 ).…”
Section: Targeting Cafs For Imagingmentioning
confidence: 99%
“…The same team also synthesized and studied the AAZTA 5 analogue of DATA 5m -SA-FAPi, following a strictly comparable synthesis sequence (Scheme 14) [84]. The broader coordination capabilities of AAZTA allowed 68 Ga, 44 Sc, and 177 Lu radiolabeling with direct comparison with DOTA-SA-FAPi.…”
Section: Fibroblast Activation Protein Inhibitorsmentioning
confidence: 99%
“…maceuticals 2022, 15, x FOR PEER REVIEW 21 of Scheme 14. Synthesis of AAZTA 5 -and DATA 5m -SA-FAPi derivatives [82,84].…”
Section: Fibroblast Activation Protein Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation